Identifying improvements to complex pathways: evidence synthesis and stakeholder engagement in infant congenital heart disease. Issue 6 (6th June 2016) - Crowe, Sonya; Knowles, Rachel; Wray, Jo; Tregay, Jenifer; Ridout, Deborah A; Utley, Martin; Franklin, Rodney; Bull, Catherine L; Brown, Katherine L
Abstract : Objectives: Many infants die in the year following discharge from hospital after surgical or catheter intervention for congenital heart disease (3–5% of discharged infants). There is considerable variability in the provision of care and support in this period, and some families experience barriers to care. We aimed to identify ways to improve discharge and postdischarge care for this patient group. Design: A systematic evidence synthesis aligned with a process of eliciting the perspectives of families and professionals from community, primary, secondary and tertiary care. Setting: UK. Results: A set of evidence-informed recommendations for improving the discharge and postdischarge care of infants following intervention for congenital heart disease was produced. These address known challenges with current care processes and, recognising current resource constraints, are targeted at patient groups based on the number of patients affected and the level and nature of their risk of adverse 1-year outcome. The recommendations include: structured discharge documentation, discharging certain high-risk patients via their local hospital, enhanced surveillance for patients with certain (high-risk) cardiac diagnoses and an early warning tool for parents and community health professionals. Conclusions: Our recommendations set out a comprehensive, system-wide approach for improving discharge and postdischarge services. This approach could be used to address challenges in delivering care for other patient populations that can fall through gaps between sectors and organisations.